2022
DOI: 10.1155/2022/6884273
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Relationship between Economic Growth and Energy Consumption from the Perspective of Sustainable Development

Abstract: While promoting the economic growth, energy has also brought pollution problems to the world environment, which has gradually become a bottleneck impeding sustainable economic development. In view of the rapid evolution of urbanization and industrialization, economic growth is increasingly dependent on the energy consumption, the development of the two is difficult to coordinate, and the internal contradictions are becoming increasingly serious, which hinders the sustainable development of economic growth. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The use of energy can increase production in a country. This is evidenced by research conducted by Dai et al, (2022) in his research entitled "Relationship between Economic Growth and Energy Consumption from the Perspective of Sustainable Development" which found that energy consumption has a significant positive effect on economic growth. Investors will be very interested in investing in countries with high economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of energy can increase production in a country. This is evidenced by research conducted by Dai et al, (2022) in his research entitled "Relationship between Economic Growth and Energy Consumption from the Perspective of Sustainable Development" which found that energy consumption has a significant positive effect on economic growth. Investors will be very interested in investing in countries with high economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The data show that the results vary widely. Researchers have found a one-way cause-and-effect relationship from economic growth to energy consumption in the short term [23,24]. Some researchers also included the economic development of national economies in their investigation.…”
Section: Reviewmentioning
confidence: 99%
“…The energy sector plays a strategic role in economic development in both developed and developing countries, thus energy availability is a crucial variable for a country's economic growth and competitiveness [1,2]. Energy consumption is often seen as a pro-growth measure, which means that an increase in energy consumption leads to an increase in economic growth [3]. Therefore, the energy sector forms the backbone of the economy, which is very important in driving the economy and supporting development.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation into the association between energy consumption and energy growth has been largely influenced by the discoveries made by Kraft and Kraft [17] who discovered a unidirectional causal relationship between economic growth and energy consumption in the United States between 1947 and 1974. Subsequent research endeavors have surfaced, leading to the classification of energy consumption into distinct categories: renewable energy and non-renewable energy [2,3,6,18,19]. However, the relationship between energy use and economic growth continues to spark debate and has yet to yield definitive results.…”
Section: Introductionmentioning
confidence: 99%